2009
DOI: 10.1021/jm8014553
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Serotonin 5-HT7 Receptor Ligands. Determinants of 5-HT7/5-HT1A Receptor Selectivity

Abstract: We report the synthesis of a new set of compounds of general structure I (1-20) with structural modifications in the pharmacophoric elements of the previously reported lead UCM-5600. The new derivatives have been evaluated for binding affinity at 5-HT(7) and 5-HT(1A) receptors. The influence of the different structural features in terms of 5-HT(7)/5-HT(1A) receptor affinity and selectivity was analyzed by computational simulations of the complexes between compounds I and beta(2)-based 3-D models of these recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…This choice was justified by reports of difficulty for some 5-HT 7 ligands in discriminating between 5-HT 1A (21,41,42) and 5-HT 6 receptors (43). We also showed that molecules of the FPMP series presented 5-HT 1A agonistic affinity (EC 50 .…”
Section: Discussionmentioning
confidence: 99%
“…This choice was justified by reports of difficulty for some 5-HT 7 ligands in discriminating between 5-HT 1A (21,41,42) and 5-HT 6 receptors (43). We also showed that molecules of the FPMP series presented 5-HT 1A agonistic affinity (EC 50 .…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the binding affinity results, a series of compounds possessing affinity below 3 nM for 5-HT 1A R (5,8,9,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and below 50 nM for 5-HT 7 receptors (9,12,15,17,18,20,21) was selected for functional profile characterization. Intrinsic activity studies were performed using in vitro measures of receptor activation.…”
Section: -21mentioning
confidence: 99%
“…Intrinsic activity studies were performed using in vitro measures of receptor activation. No activation of any of the receptors was observed, and the compounds showed antagonist properties, especially the 5-HT 1A (5,9,12,14,15,(17)(18)(19)(20)(21) (Figures 4 and 5). In case of 5-HT 7 R, there are significant differences between the binding and functional tests results for selected compounds.…”
Section: -21mentioning
confidence: 99%
See 1 more Smart Citation
“…Many ligands have been reported to bind with high affinity to 5-HT 7 receptors and their number is continuously increasing. [17][18][19] In the course of a program aimed at the discovery of new serotonine 5-HT 7 ligands, we submitted to binding assays a range of N-substituted (5-methoxy-3,4-dihydro-2H-1-benzopyran-3-yl)amine derivatives previously studied as 5-HT 1A receptor ligands. [20][21][22] We found that two of them (5-MeO-DPAC and S 20244) displayed significant affinity for 5-HT 7 R. Subsequently, we planned This lack of selectivity has led us to translate the knowledge acquired in the benzopyran series, to aminopyrrolothienopyrazine series, which has been described recently as being the possible support of new 5-HT ligands.…”
Section: Introductionmentioning
confidence: 99%